PENGARUH ATTRIBUTE PRODUCT TERHADAP CUSTOMER LOYALTY YANG DIMEDIASI OLEH CUSTOMER SATISFACTION PADA PEMAIN GAME PUBG MOBILE DI KOTA BANDUNG - Mochamad Haikal Ardiansyah; Hariyadi Triwahyu Putra (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
. This study aims to understand the influence of product attributes on customer loyalty, with customer satisfaction serving as a mediating variable, specifically among active PUBG Mobile players residing in Bandung. Data were collected from 120 respondents, all of whom belong to Generation Z and actively engage with the game. The research instrument used in this study had previously undergone validity and reliability tests, ensuring its quality. Data analysis was conducted using simple and multiple linear regression techniques with the assistance of SPSS version 27. Additionally, the Sobel test was employed to examine the mediating role of customer satisfaction. The results of the study revealed that product attributes have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction was found to positively influence customer loyalty. Regression analysis also indicated that product attributes have a direct impact on customer loyalty, and this relationship becomes stronger when customer satisfaction acts as a mediating variable